2006
DOI: 10.1364/jon.5.000435
|View full text |Cite
|
Sign up to set email alerts
|

Optical network architectures for dynamic reconfiguration of full duplex, multiwavelength, radio over fiber

Abstract: In recent years there have been rapid advances in the techniques to generate and transport radio signals over optical fibre, however very little has been done to date to develop the concept of a full duplex, multi-wavelength, radio -over-fibre network architecture that intrinsically supports and facilitates the dynamic reconfiguration of the wireless network. Recently the development of suitable architectures has received attention, with some approaches concentrating on the fibre radio link layer [ 1] and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Considering analogue transport methods, a number of challenges occur when RoF channels are overlaid on baseband PON wavelengths. The most difficult of these is how to address the individual BSs connected to the PON when the physical architecture is broadcast and select [38]. Solutions involve either wavelength or RF mapping techniques to route wireless channels to specific end points.…”
Section: B Wavelength Overlay In Current Standardsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering analogue transport methods, a number of challenges occur when RoF channels are overlaid on baseband PON wavelengths. The most difficult of these is how to address the individual BSs connected to the PON when the physical architecture is broadcast and select [38]. Solutions involve either wavelength or RF mapping techniques to route wireless channels to specific end points.…”
Section: B Wavelength Overlay In Current Standardsmentioning
confidence: 99%
“…The generic set of options for multi-wavelength networks were demonstrated in [38] where systems where categorized depending on the method and degree of wavelength selectability they afforded. The use of a sub-set of the wavelengths, provides a basic backhaul functionality, however, the availability of a full-duplex, WDM overlay, capable of delivering RoF services coupled with a centralized pool of baseband processing units provides a degree of reconfigurability not currently available.…”
Section: B Wavelength Overlay In Current Standardsmentioning
confidence: 99%
“…In order to serve multiple users, previous research has suggested transport of multiple data modulated signals over several fibers [5]. Work has been done on the use of DWDM to transport multiple signals over a single fiber [6], however, subcarrier multiplexing (SCM) is preferred due to the cost and stringent tolerances of the optical components for the DWDM based system [7].…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the centralization capabilities offered by RoF, significant investment and operational cost savings are expected. Preliminary studies [2] have demonstrated the possibility to achieve broadband ubiquity by optimizing in real-time the coverage and the capacity of the radio system. Two variants of RoF are today available: Analog RoF (A-RoF) and Digitized RoF (D-RoF).…”
Section: Introductionmentioning
confidence: 99%